2017
DOI: 10.1016/j.celrep.2016.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Sema-1a Reverse Signaling Promotes Midline Crossing in Response to Secreted Semaphorins

Abstract: SUMMARY Commissural axons must cross the midline to form functional midline circuits. In the invertebrate nerve cord and vertebrate spinal cord, midline crossing is mediated in part by Netrin-dependent chemoattraction. Loss of crossing, however, is incomplete in mutants for Netrin or its receptor Frazzled/DCC, suggesting the existence of additional pathways. We identified the transmembrane Semaphorin, Sema-1a, as an important regulator of midline crossing in the Drosophila CNS. We show that in response to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Several studies have shown that the signalling activities and interactions of class-6 semaphorins are regulated by a complex combination of cis-and trans-interactions with plexin A receptors (Haklai-Topper et al, 2010;Andermatt et al, 2014;Perez-Branguli et al, 2016). A role for membranebound Semaphorin 1a has also been shown for midline crossing in invertebrates, although in this case the effect was found to be independent of Plexin binding (Hernandez-Fleming et al, 2017).…”
Section: Regulation At the Post-translational Levelmentioning
confidence: 98%
“…Several studies have shown that the signalling activities and interactions of class-6 semaphorins are regulated by a complex combination of cis-and trans-interactions with plexin A receptors (Haklai-Topper et al, 2010;Andermatt et al, 2014;Perez-Branguli et al, 2016). A role for membranebound Semaphorin 1a has also been shown for midline crossing in invertebrates, although in this case the effect was found to be independent of Plexin binding (Hernandez-Fleming et al, 2017).…”
Section: Regulation At the Post-translational Levelmentioning
confidence: 98%
“…In vitro, contextdependent switch from attraction to repulsion and vice-versa were evidenced for a large range of guidance molecules including Netrins, Semaphorins, and Slits (Höpker et al, 1999;Castellani et al, 2000;Nguyen-Ba-Charvet et al, 2001;Castellani et al, 2002;Ma et al, 2007). In vivo, although considered as repellents, Sema2a and Sema3B were recently reported to promote midline crossing in drosophila, acting as chemoattractant via Sema1a (Hernandez-Fleming et al, 2017).…”
Section: Commissural Axon Navigation Is Driven By Restriction Of Growmentioning
confidence: 99%
“…This indicates that additional pathways must promote midline crossing [ 11 , 12 ]. Indeed, several additional factors implicated in promoting midline axon attraction have been identified in invertebrate and vertebrate systems, such as Shh/Boc [ 13 ], Sema2a/Sema1a [ 14 ], and VEGF/Flk1 [ 15 ]. In addition, many other mechanisms have been described that promote axon growth across the midline by preventing premature responses to repulsive molecules secreted from the midline, such as Slits and Semaphorins [ 16 20 ].…”
Section: Introductionmentioning
confidence: 99%